Nε-(carboxymethyl) lysine and corony atherosclerosis-associated low density lipoprotein abnormalities in type 2 diabetes: current status - Ismail, I.S.; Ahmed, K.A.; Muniandy, S. (Institute of Applied Biochemistry, 2009)
In comparison to the general population, individuals with diabetes suffer a 3- to 4- fold increased risk for developing complications of atherosclerosis and vascular insufficiency. This fact should be taken into account to develop a suitable determinant for the early detection of these complications and subsequently reduce the adverse effect of type 2 diabetes. In vitro experiments have shown that the products of glucose auto-oxidation and Amadori adducts are both potential sources of Nε-(carboxymethyl)lysine (CML). Excessive formation of CML on low density lipoprotein (LDL) has been proposed to be an important mechanism for the dyslipidemia and accelerated atherogenesis observed in patients with type 2 diabetes. It has been postulated that the uptake of CML-LDL by LDL receptors is impaired, thereby decreasing its clearance from the blood circulation. Alternatively, the uptake of these modified LDL particles by scavenger receptors on macrophages and vascular smooth muscle cells (SMCs) and by AGE receptors on endothelial cells, SMCs, and monocytes is highly enhanced and this, in turn, is centrally positioned to contribute to the pathogenesis of diabetic vascular complications especially coronary artery disease. The present review summarizes the up-to-date information on effects and mechanism of type 2 diabetes-associated coronary atherosclerosis induced by CML-LDL modification.